Martin Luther King, Jr. the last interview and other conversations - King, Martin Luther 1929-1968 (Melville House, 2017)
"As the Black Lives Matter movement gains momentum, and books like Ta-Nehisi Coates's Between the World and Me and Claudia Rankine's Citizen swing national attention toward the racism and violence that continue to poison our communities, it's as urgent now as ever to celebrate Martin Luther King, Jr., whose insistence on equality and peace defined the Civil Rights Movement and forever changed the course of American history. This collection ranges from an early 1961 interview in which King describes his reasons for joining the ministry (after considering medicine), to a 1964 conversation with Robert Penn Warren, to his last interview, which was conducted on stage at the convention of the Rabbinical Assembly, just ten days before King's assassination. Timely, poignant, and inspiring, Martin Luther King, Jr.: the last interview is an essential addition to the Last Interview series"...
Keywords: King, Martin Luther -- Jr. -- 1929-1968 -- Interviews; King, Martin Luther -- Jr. -- 1929-1968 -- Political and social views; King, Martin Luther -- 1929-1968; Geschichte 1900-2000; Geschichte 1957-1968; BIOGRAPHY & AUTOBIOGRAPHY / Political; BIOGRAPHY & AUTOBIOGRAPHY / Cultural Heritage; Geschichte; Klerus; Schwarze. USA; African American civil rights workers -- Interviews; Civil rights workers -- United States -- Interviews; Baptists -- United States -- Clergy -- Interviews; African Americans -- Civil rights -- History -- 20th century -- Sources; Civil rights movements -- United States -- History -- 20th century -- Sources; Bürgerrechtsbewegung; USA; United States -- Race relations -- History -- 20th century -- Sources; Interview; Quelle